Penentuan Kelayakan Pemberian Kredit Menggunakan Metode SAW Pada PT. Leasing Arthaprima Finance Kotamobagu - Arundaa, Rillya; Pekuwali, Arini Aha (Journal of Data Science and Information Systems, 2024)
In cash loan credit service companies, the determination of creditworthiness to consumers is carried out by the credit analyst. The Credit Analyst Department is required to work quickly and thoroughly in the selection of the number of incoming credit applications so that it does not rule out the possibility of miscalculations, misreading data, and so on. This study aims to apply the SAW method in determining credit consumers who are eligible for credit loans. There are 4 criteria used, namely Personality, Ability, Credit Guarantee, and Economic Conditions. In determining the eligibility of credit, 2 comparative values are used, namely the eligibility criteria (value 60) and the current criteria (value 100). Consumers are declared eligible for cash credit loans if the calculation of the preference value is more than 60. According to the calculation results in 10 alternative data, 7 consumers were obtained who were eligible for cash loan loans and 3 consumers who were rejected because their preference values did not meet the threshold value.